Applying Lanna Culture to Develop Film Media through Action Research - Kritsunthon, Parin; Kittiwarakul, Nantasit (Journal for Developing the Social and Community, 2024)
The creative industries are a vital sector contributing significantly to Thailand's economy. This study aims to investigate the application of Lanna history and culture in film production. It is part of the project titled *“Research and Development to Elevate Thai Film Production to the Global Market and Develop Internationally Competent Human Resources Using Lanna History and Culture.” This project is funded by the Thailand Science Research and Innovation Administration Division (TSRI) through a participatory action research approach. The study's findings are summarized as follows: 1. Application of Lanna Culture: Lanna cultural elements were incorporated into five films through themes such as beliefs, arts, performing arts, cuisine, and local festivals. 2. Cultural Recognition: The films effectively enhanced audience recognition and awareness of Lanna culture. 3. Economic Dimension: Films demonstrated the potential to promote film tourism among viewers. For filmmakers, film production contributed to local economic growth by utilizing provincial locations for shooting. 4. Cultural Dimension: While cultural elements were included, filmmakers were not sufficiently effective in presenting Lanna culture comprehensively. Audiences needed prior knowledge of Lanna culture to fully engage with the films. This contrasts with more familiar cultural narratives, such as Isan culture, which viewers typically have foundational knowledge of. The study concludes that Lanna culture is intricate and multifaceted, making it challenging to convey its essence fully through a single medium such as film. Familiarizing audiences with Lanna culture requires the integration of other media platforms. Despite its strong cultural potential, Lanna culture's development is hindered by a lack of opportunities and support at local and provincial levels. Enhancing access and providing platforms for local filmmakers are critical to fostering a sustainable and robust local film industry.